Pengaruh Kompetensi Kepribadian Guru terhadap Akhlak Siswa di SMK Cendekian Muslim Nanggung-Bogor - Evi Safitri; Yanti Hasbian Setiawati; Agus Suryana (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
Islamic religious education teachers are often targeted and cornered when many students violate school rules and regulations. But with the personality competence of Islamic religious education teachers, students can imitate the attitudes and actions of their teachers. This research was conducted at SMK Cendikia Muslim Nanggung Bogor. The research population was 832 students while the sample was 40 students, with a stratified random sampling technique. This study applies the correlation method with research instruments using a questionnaire for the personality competence of Islamic religious education teachers and student morals using a questionnaire. The data were analyzed using the product moment correlation technique. The results showed that r count = 0.731, which means that there is an influence of the personality competence of Islamic religious education teachers on student morals. Likewise, the significance test with the t test shows t count 6.603 t table 2.024, this means that the influence of personality competences of Islamic religious education teachers has a significant effect. While the contribution of Islamic religious education teachers to student morals is shown by the coefficient of determination = 53% which means that the personality competence of Islamic religious education teachers makes a large contribution to student morals.